Making an eco friendly board by using lignin- soy based natural adhesive - Ema Farima, Rustam Ali Khan (2012)
The wood composite industry in Malaysia comprises of 12 MDF and 10 particleboard plants with an installed capacity of about 5 million tons per year.The total production capacity is approx 2.5 million cubic ton.Most of the MDF boards are exported to US,Europe and Asian market.At present formaldehyde based adhesive such as urea formaldehyde(UF) and phenol formaldehyde(PF)is used as the binder.The main problem with these adhesives is continuous emission of formaldehyde vapors that are carcinogenic in nature.A number of developed countries have put ban on the import of these boards.The objective of this research is to modify the lignin content of wood fibers by using soy flour which is available in Malaysia.This modified lignin based adhesive is expected to replace the use of artificial resins like UF and PF and because of commonly available soy flour it will be economical and eco friendly.The fiberboards were prepared from three different adhesives, which are urea formaldehyde (UF) resins, natural adhesive (lignin) and protein-lignin based adhesives.Hot pressing at constant temperature 180ºC and pressure 2MPa within 4 minutes pressing was done to form the boards.For each board were tested for mechanical properties including modulus of rupture (MOR),thickness swelling (TS) and internal bond strength (IB).Results showed that SF,lignin,acetic acid (CH3COOH) and sodium hydroxide were all essential components for the adhesive and the SF: lignin:CH3COOH weight ratio of 3:75:10 with pH 11 resulted in the highest value of MOR, IB strength and water resistance. Fiberboard made from lignin- soy based natural adhesive shows promise and possibilities for industrial application in wood composite industries.Moreover,lignin- soy based adhesive used resulting in boards with good mechanical properties without toxic effect to humans.